Clinical and molecular monitoring of Plasmodium falciparum resistance to antimalarial drug (artesunate+sulphadoxine-pyrimethamine) in two highly malarious district of Madhya Pradesh, Central India from 2012–2014. (19th May 2017) - Mishra, Sweta; Bharti, Praveen K.; Shukla, Man M.; Ali, Nazia A.; Kashyotia, Sher S.; Kumar, Avdhesh; Dhariwal, Akshay C.; Singh, Neeru
Abstract: The spread of P. falciparum resistant strain has led to a significant resurgence of malaria morbidity and mortality. The current cornerstone in malaria treatment in India is Artemisinin based Combination (Artesunate + Sulphadoxine-Pyrimethamine) Therapy (ACT) for treatment of uncomplicated P. falciparum malaria since 2010. In the present study we assessed the therapeutic efficacy of ACT and molecular monitoring of antimalarial resistance. Therapeutic efficacy was determined by in vivo method using 28 days follow-up. Molecular genotyping of dihydrofolate reductase ( dhfr ), dihydropteroate synthase ( dhps ) and kelch13 genes were analyzed. msp - 1 and msp -2 genotyping were used to differentiate recrudescence. Therapeutic efficacy of ACT was determined in 237 patients over the three year period. Most of the patients showed adequate clinical and parasitological response (99.6%). Molecular study revealed that 72% parasites were of mutant genotype (27.2% single mutants, 43.5% double mutants and 1.3% triple mutants) for pfdhf r while pfdhps showed 78.2% wild type alleles and 21.8% mutants (18.1% single mutants and 3.7% double mutants). Analysis of total 135 samples revealed mutation in k13 gene along with non-synonymous single mutation at codon M579T (1.5%) and double mutations at codon M579T & N657H in 37%. ACT remains effective for the treatment of uncomplicated P. falciparum malaria in Madhya Pradesh, Central India. However, increasing mutation in pfdhfr (particularly triple mutations) and pfdhps may reduce susceptibility to partner drug SP and mutation in k13 propeller gene, highlighting the need for continuous monitoring of the efficacy of ACT. Abstract :